A Population-Based Cohort Analysis of Chemoradiation Versus Radiation Alone for Definitive Treatment of Stage I Anal Cancer in Older Patients. Issue 7 (July 2018) - Buckstein, Michael; Arens, Yotam; Wisnivesky, Juan; Gaisa, Michael; Goldstone, Stephen; Sigel, Keith
Abstract : BACKGROUND: Although the benefit of chemoradiation over radiation therapy alone has been shown in randomized trials for stage II to III squamous cell of the anus, this benefit is not clear for patients with stage I cancer. Nevertheless, most societal recommendations endorse chemoradiation for patients with stage I squamous cell carcinoma of the anus despite the lack of proven benefit and potential increase in toxicity. OBJECTIVE: The purpose of this study was to determine whether outcomes are improved with the addition of chemotherapy versus radiation alone for stage I squamous cell carcinoma of the anus. DESIGN: This was a cohort analysis using Surveillance, Epidemiology and End Results registry linked to Medicare from 1996 to 2011. Propensity-score methods were used to control for potential confounding. SETTINGS: This was a population-based study. PATIENTS: Medicare eligible patients (age >65 y or with an eligible disability) with stage I squamous cell carcinoma of the anus treated with either definitive radiation alone or chemoradiation were included. INTERVENTIONS: Radiation or chemoradiation was the intervention. MAIN OUTCOME MEASURES: Overall survival, disease-free survival, cause-specific survival, colostomy-free survival, and acute or late toxicities were measured. RESULTS: A total of 200 patients with squamous cell carcinoma of the anus were identified who received chemoradiation versus 99 treated with lone radiotherapy. Median age was 72 years and did not differ by treatment ( p = 0.6). Patients receiving chemoradiation had improved unadjusted overall survival compared with lone radiotherapy, but after adjustment using propensity-score methods there was no difference in overall survival (HR = 0.7 (95% CI, 0.4–1.0)), cause-specific survival (HR = 0.7 (95% CI, 0.3–1.6)), colostomy-free survival (HR = 1.1 (95% CI, 0.5–2.5)), or disease-free survival (HR = 0.9 (95% CI, 0.6–1.4)). Chemoradiation was associated with an increased risk of select early and late toxicities. LIMITATIONS: This is a retrospective series from an anonymous database. The data might not be relevant for younger, healthier patients. CONCLUSIONS: Lone radiation may be associated with adequate oncologic outcomes when used to treat older and sicker patients with stage I anal cancer. Physicians should discuss the potential benefits and harms of adding chemotherapy for the treatment of these patients. SeeVideo Abstract athttp://links.lww.com/DCR/A628 .